Chickadee - Erdrich, Louise (Erdrich, Louise. Birchbark House series, 2012)
In 1866, Omakayas's son Chickadee is kidnapped by two ne'er-do-well brothers from his own tribe and must make a daring escape, forge unlikely friendships and set out on an exciting and dangerous journey to get back home.